Centrica : strategizing in a multi-utility - Paroutis, Sotirios, (SAGE Knowledge. Cases., 2016)
The case describes how Sir Roy Gardner became CEO of Centrica after its demerger from British Gas and turned the failing company around for it eventually to become a success. Roy Gardner replaced the old utility model they had inherited from British Gas and instead developed a business model where customer satisfaction and retention would be central.